Effects of Ionic Liquid Additive Concentration on Scuffing and Wear in Oil-Starved EHL Contacts. Issue 6 (2nd November 2018) - Murthy, Nikhil; Berkebile, Stephen; Rai, Amarendra K.; Hille, Eric; Ewin, Jeffrey
Abstract: We show how various concentrations ranging from 0 to 5.0 wt% of the ionic liquid (IL) trihexyltetradecylphosphonium bis(2-ethylhexyl)phosphate added to a fully formulated aviation DOD-PRF-85734 gearbox lubricant affects the properties of the lubricant, including scuffing resistance under starved lubrication conditions, coefficient of friction (COF), wear rate, and lubricant chemical stability. Specimen surfaces were then characterized using scanning electron microscopy, energy-dispersive spectroscopy, and auger electron spectroscopy. Scuffing and wear properties were found to generally improve with IL concentration, which we hypothesize is due to the presence of a phosphorous-rich film observed on specimens exposed to IL.